10-2(x+3)=-5x+6

Simple and best practice solution for 10-2(x+3)=-5x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-2(x+3)=-5x+6 equation:


Simplifying
10 + -2(x + 3) = -5x + 6

Reorder the terms:
10 + -2(3 + x) = -5x + 6
10 + (3 * -2 + x * -2) = -5x + 6
10 + (-6 + -2x) = -5x + 6

Combine like terms: 10 + -6 = 4
4 + -2x = -5x + 6

Reorder the terms:
4 + -2x = 6 + -5x

Solving
4 + -2x = 6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
4 + -2x + 5x = 6 + -5x + 5x

Combine like terms: -2x + 5x = 3x
4 + 3x = 6 + -5x + 5x

Combine like terms: -5x + 5x = 0
4 + 3x = 6 + 0
4 + 3x = 6

Add '-4' to each side of the equation.
4 + -4 + 3x = 6 + -4

Combine like terms: 4 + -4 = 0
0 + 3x = 6 + -4
3x = 6 + -4

Combine like terms: 6 + -4 = 2
3x = 2

Divide each side by '3'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| 7(n+5)=35+7n | | 5c^4+10c^2+5= | | 7x+8=7(x+2) | | -2b=9-3a | | 1+4x=9+2x | | X^3-21x^2+120x=0 | | 3X^2(2X^3+8X^2-5X+6)= | | -11=3u+7 | | 24+6k=4(k+4) | | 5(2x+8)=2x-64 | | 20m=420 | | 6+2y=-4 | | 2y=-7x+10 | | 4(7x+8)=32 | | -5(a+4)=-11-8a | | -8+(-4)=q | | 3(3x+8)=9x-1 | | 7q=11+p | | 4(x+2)-2x=20-2x | | x-3=7x+28 | | 45+x=47 | | 84=4w*8 | | 4.2+4(4.2)+2=23 | | 1240=220*t | | 14=-(p-8)b | | -(7x-2)=X-30 | | -0.5*32x^2+48x+0=20 | | 8+2x=2+3x | | (x-3)+4=9 | | P*60=1080 | | -156=-4 | | 10x-7=-47 |

Equations solver categories